Optimizing port system resilience through integrated preparedness and recovery strategies - Xing, Zheng; Zhou, Chenhao; Shen, Yu; Chew, Ek Peng; Tan, Kok Choon (Reliability engineering & system safety, 2026)
Ports, recognized as intricate systems, are susceptible to a variety of human-induced incidents and natural phenomena that can result in disruptions. Strengthening the port’s ability to manage disruptions and bolstering the resilience of the port system play a crucial role in ensuring the smooth operation of commercial trade. Nevertheless, assessing the port’s resilience and making decisions regarding pre- and post-disruption actions in uncertain circumstances present notable challenges. This research delves into the topic of network resilience within port logistics and operational infrastructure, introducing a novel indicator for evaluating port resilience. Moreover, the study frames this issue as a stochastic mixed-integer linear programming (SMILP), determining preparedness and recovery measures to enhance the resilience of the port system. Subsequently, a double-decomposed methodology is suggested for resolving the model, which incorporates Lagrangian Decomposition and a branch-and-price algorithm utilizing Dantzig–Wolfe Decomposition. Ultimately, the efficacy of the algorithm and the significance of the strategies in risk management are validated through a practical case study.